Types of Directive Illocutionary Acts in Barbie Movie (Lembaga Pengembangan Kinerja Dosen, 2024)
This article analyzed the six types of directive illocutionary acts that used by the main character in Barbie movie, named Barbie Margot. The aims of this article is to find out the types of directive illocutionary acts that used by the main character in Barbie movie. The descriptive method used to analyzed the data source based on Allan (1986) theory on six types of directive illocutionary acts and the theory of context situation byHolmes (2013) as a support theory to identifying the data. The data was collected using observing method with the technique of listening, reading, documentation and note taking to observe and collect the data. As a result this article showed that the Barbie Margot used four types of directive illocutionary acts, there are; requirement (1), request (2). question (4) and prohibition (2).